Lithium-ion cylindrical battery, electric device
Patent Information
- Application Number
- CN202611121137.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-27
- Publication Date
- 2026-10-13
AI Technical Summary
1、本发明通过限定底涂层厚度、常温面电阻、受热电阻升高倍数和正极压实密度的范围并定义SPI判据,使电池正常工况下保持低内阻、低极化和高能量密度,而在内短路发生时短路点附近的底涂层因焦耳热引起电阻急剧升高,形成高阻限流通道,从而将针刺或热滥用条件下的内部短电流抑制在安全范围内。
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery technology, and more specifically, to a lithium-ion cylindrical battery and an electrical device. Background Technology
[0002] Cylindrical lithium-ion batteries, especially all-tab cylindrical batteries using high-energy-density cathode materials, are prone to internal short circuits when subjected to extrusion, puncture, metal foreign object penetration, or lithium dendrite penetration of the separator. The instantaneous large current at the short circuit point generates Joule heat, which can easily lead to thermal runaway. Therefore, effectively suppressing thermal runaway caused by internal short circuits while improving battery energy density and power output is an urgent technical problem to be solved. Summary of the Invention
[0003] In view of this, the present invention aims to at least partially solve one of the technical problems in the related art. To this end, the present invention provides a lithium-ion cylindrical battery and an electrical device that, by limiting the thickness of the undercoating layer, the surface resistance at room temperature, the resistance increase factor after heating, and the compaction density of the positive electrode sheet, and combining these with the full tab welding coverage η, constitutes an internal short-circuit protection index SPI ≥ 3.2. This allows the battery to maintain low internal resistance, low polarization, and high energy density under normal operating conditions, while forming a high-resistance current-limiting channel when internal short circuits occur due to needle penetration or thermal abuse, thereby effectively preventing thermal runaway.
[0004] To solve the above-mentioned technical problems, the present invention is implemented as follows: According to one aspect of the present invention, a lithium-ion cylindrical battery is provided, comprising a positive electrode sheet, the positive electrode sheet comprising a positive current collector, a positive active material layer disposed on at least one side of the positive current collector, and a base coating layer disposed between the positive current collector and the positive active material layer; The thickness of the base coating is 0.5µm to 5µm; The sheet resistance of the base coating at 25°C is R = 5 Ω·cm. 2 ~80Ω·cm 2 ; The resistivity increase factor K of the base coating after heating at 130°C is 4~20, where K is the ratio of the surface resistivity of the base coating after heating at 130°C to the surface resistivity at 25°C. The compaction density of the positive electrode is 3.20 g / cm³. 3 ~3.60g / cm 3 ; The lithium-ion cylindrical battery has a full tab laser welding structure, and the full tab welding coverage is η, where η is the ratio of the tab laser welding area to the effective area of the tab end face. The lithium-ion cylindrical battery satisfies the internal short-circuit protection index SPI=K×η≥3.2.
[0005] In some of these implementations, η ≥ 80%.
[0006] In some of these implementations, SPI = 3.2~17.
[0007] In some embodiments, the undercoat layer comprises one or more of the following: a composite layer containing a polymer matrix with a positive temperature coefficient and a conductive filler, an insulating-semi-conductive layer dispersed in nano-alumina, and a polyimide-based high-resistivity layer.
[0008] In some of these embodiments, the crystallinity of the positive temperature coefficient polymer matrix is 30% to 82%.
[0009] In some of these embodiments, the conductive filler has a mass fraction of 1% to 10%.
[0010] In some embodiments, the positive electrode active material layer includes a positive electrode active material with the general chemical formula LiNi. x Co y Mn z O2, where 0.8≤x<1, x+y+z=1.
[0011] In some embodiments, the core further includes a negative electrode sheet comprising a negative electrode active material, which comprises a silicon-carbon composite material and / or graphite.
[0012] In some embodiments, the lithium-ion cylindrical battery is a 21650 cylindrical battery.
[0013] In some embodiments, the lithium-ion cylindrical battery has an outer diameter of 21 mm, a total height of 65 mm, and a core height of 62.3 mm.
[0014] In some of these embodiments, the initial DC internal resistance of the lithium-ion cylindrical battery is ≤10mΩ.
[0015] In some of these embodiments, the lithium-ion cylindrical battery retains ≥83% of its capacity after 500 cycles at 1C rate at 25°C.
[0016] In some of these embodiments, the DC internal resistance growth rate of the lithium-ion cylindrical battery after 500 cycles at 1C rate at 25°C is ≤20%.
[0017] In some of these embodiments, the lithium-ion battery, when fully charged, is subjected to a needle puncture test with a steel needle of 3 mm diameter at a puncture speed of 25 mm / s. Within 300 seconds, the highest surface temperature is ≤150°C, and no fire or explosion occurs.
[0018] In some of these embodiments, the lithium-ion battery remained free from fire or explosion for 30 minutes in a 130°C hot box test.
[0019] In some embodiments, the base coating further includes an adhesive comprising one or more of polyvinylidene fluoride and its copolymers, polyacrylic acid, polyimide, polyacrylonitrile, polyurethane, sodium carboxymethyl cellulose, and styrene-butadiene rubber.
[0020] According to one aspect of the present invention, an electrical device is provided, comprising the lithium-ion cylindrical battery described in the above technical solution.
[0021] Implementing the technical solution of the present invention has at least the following beneficial effects: 1. This invention limits the range of base coating thickness, surface resistance at room temperature, increase factor of resistance under heat, and positive electrode compaction density, and defines the SPI criterion to maintain low internal resistance, low polarization, and high energy density of the battery under normal operating conditions. When an internal short circuit occurs, the resistance of the base coating near the short circuit point increases sharply due to Joule heating, forming a high-resistance current-limiting channel, thereby suppressing the internal short current under needle penetration or thermal abuse conditions within a safe range.
[0022] 2. This invention establishes a low-cost evidence criterion for short-circuit current limiting protection within a full-tab structure. The parameters can be reverse-verified using low-cost methods such as cross-sectional scanning electron microscopy, four-probe, needle penetration, and hot box, without relying on high-cost characterization equipment such as XRD / XPS.
[0023] Additional aspects and advantages of the invention will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of the invention. Detailed Implementation
[0024] The present application will be further described below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the present application.
[0025] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges or individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0026] In the description of this application, "same chemical composition" should be interpreted broadly, that is, the main components of the two have the same chemical composition, or the two have substantially the same chemical composition, but may have errors or impurities within the acceptable range that can be understood by those skilled in the art.
[0027] In the description of this application, "A and / or B" can include any of the cases of A alone, B alone, or A and B, where A and B are merely examples and can be any technical feature connected by "and / or" in this application.
[0028] Unless otherwise specified, the terms "comprising" and "including" as used in this invention can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.
[0029] Unless otherwise specified, all embodiments and optional embodiments of the present invention can be combined with each other to form new technical solutions.
[0030] Unless otherwise specified, all technical features and optional technical features of this invention can be combined to form new technical solutions.
[0031] Unless otherwise specified, all steps of the present invention may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the mention that the method may also include step (c) indicates that step (c) may be added to the method in any order; for example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.
[0032] Cylindrical lithium-ion batteries, especially all-tab cylindrical batteries using high-energy-density cathode materials, are prone to internal short circuits when subjected to extrusion, puncture, metal foreign object penetration, or lithium dendrite penetration of the separator. The instantaneous large current at the short circuit point generates Joule heat, which can easily lead to thermal runaway. Therefore, effectively suppressing thermal runaway caused by internal short circuits while improving battery energy density and power output is an urgent technical problem to be solved.
[0033] To address the issue of internal short-circuit thermal runaway, the inventors discovered that existing technologies often introduce a high-resistivity functional undercoat between the positive electrode aluminum foil and the active layer. This undercoat can form a high-resistivity current-limiting channel near the short-circuit point during an internal short circuit, and further increase resistance upon heating by utilizing the positive temperature coefficient (PTC) of the undercoat material, thereby suppressing short-circuit current and delaying or blocking thermal runaway. However, existing undercoats are mostly used to improve adhesion or conductivity, and generally lack a scheme to synergistically correlate key parameters such as undercoat thickness, surface resistance at room temperature, the increase factor of resistance under heat, and positive electrode compaction. Furthermore, existing technologies cannot perform reverse verification of the internal short-circuit protection effect on finished batteries using low-cost and repeatable methods. In particular, when pursuing a full-tab structure to reduce normal DC internal resistance (DCR), there is a lack of clear technical basis for setting quantitative criteria for the above parameters to achieve a verifiable engineering balance between normal low polarization and abnormal high current limiting.
[0034] Therefore, how to provide a quantifiable and verifiable internal short-circuit protection design while ensuring low internal resistance, high energy density and long cycle life of the battery under normal conditions, and thus simultaneously achieve the ultimate safety goal of no fire and no thermal runaway, has become an urgent technical problem to be solved.
[0035] Based on this, the present invention provides a layer with a thickness of 0.5µm to 5µm and a surface resistivity of 5Ω·cm at room temperature between the positive electrode current collector and the positive electrode active material layer. 2 ~80Ω·cm 2 Furthermore, the base coating, whose resistance increases by 4 to 20 times after heating, together with the full tab welding coverage η, constitutes an internal short-circuit protection index SPI ≥ 3.2. This allows the battery to maintain low internal resistance and low polarization under normal operating conditions. However, when internal short circuits occur due to needle penetration or thermal abuse, the resistance of the base coating near the short circuit point increases sharply due to Joule heating, forming a high-resistance current-limiting channel. This suppresses the internal short-circuit current within a safe range, thereby effectively preventing thermal runaway. At the same time, it also takes into account low DC internal resistance and good cycle life.
[0036] According to one aspect of the present invention, a lithium-ion cylindrical battery is provided, comprising a core, the core comprising a positive electrode sheet, the positive electrode sheet comprising a positive current collector, a positive active material layer disposed on at least one side of the positive current collector, and a base coating layer disposed between the positive current collector and the positive active material layer; The thickness of the base coating is 0.5µm to 5µm; The sheet resistance of the base coating at 25°C is R = 5 Ω·cm. 2 ~80Ω·cm 2 ; The resistivity increase factor K of the base coating after heating at 130°C is 4~20, where K is the ratio of the surface resistivity of the base coating after heating at 130°C to the surface resistivity at 25°C. The compaction density of the positive electrode is 3.20 g / cm³. 3 ~3.60g / cm 3 ; The lithium-ion cylindrical battery has a full tab laser welding structure, and the full tab welding coverage is η, where η is the ratio of the tab laser welding area to the effective area of the tab end face. The lithium-ion cylindrical battery satisfies the internal short-circuit protection index SPI=K×η≥3.2.
[0037] In a specific embodiment of the present invention, the lithium-ion cylindrical battery includes a positive electrode sheet, which includes a positive current collector, a positive active material layer disposed on at least one side of the positive current collector, and a base coating layer disposed between the positive current collector and the positive active material layer. After discharging the finished battery to 0% state of charge, the positive electrode sheet is disassembled in a dry environment, cleaned with dimethyl carbonate (DMC), vacuum dried, polished by argon ion beam cross-section, and observed by field emission scanning electron microscopy (CP-SEM). The three-layer structure of aluminum foil / base coating layer / positive active material layer can be distinguished. The continuous coverage area ratio of the base coating layer along the coating area is statistically analyzed in multiple fields of view, i.e., the continuous coverage rate. The continuous coverage rate of the base coating layer along the coating area of the positive current collector is ≥95%.
[0038] In a specific embodiment of the present invention, the thickness of the undercoating layer is 0.5µm to 5µm, specifically 0.5µm, 1.0µm, 1.5µm, 2.0µm, 2.5µm, 3.0µm, 3.5µm, 4.0µm, 4.5µm, 5.0µm, and any value between the two mentioned above. The thickness of the undercoating layer determines the geometric thickness of the current-limiting layer and its series current-limiting capability. If the thickness is too small, the undercoating layer is too thin and the continuous coverage is insufficient, resulting in insufficient current-limiting capability to suppress thermal runaway; if the thickness is too large, although the needle penetration safety is good, the positive electrode series resistance increases significantly and occupies the internal space of the battery, leading to a decrease in energy density and rate performance.
[0039] In a specific embodiment of the present invention, the sheet resistance R of the base coating at 25°C is measured on the aluminum foil coated with the base coating using a four-probe method, and the sheet resistance R of the base coating at 25°C is 5 Ω·cm. 2 ~80Ω·cm 2 Specifically, it can be 5Ω·cm 2 10Ω·cm 2 20Ω·cm 2 30Ω·cm 2 40Ω·cm 2 50Ω·cm 260Ω·cm 2 70Ω·cm 2 80Ω·cm 2 The surface resistivity of the primer coating at room temperature reflects its conductivity under normal operating conditions, and its magnitude is determined by the content of conductive filler in the primer coating and the percolation network density. A lower R results in lower normal polarization and lower DC internal resistance, but weaker current-limiting capability during internal short circuits; a higher R results in stronger current-limiting capability, but greater normal DC internal resistance and polarization. If R is too small, the conductive network is too dense, and the primer coating is almost a conductive layer with virtually no current-limiting capability; if R is too large, the normal positive electrode contact resistance is too high, polarization is severe, and the rate and capacity do not meet the standards. This invention uses the surface resistivity R of the primer coating at 25°C to balance internal short-circuit current limiting and normal low polarization, solving the technical problem of "the more insulating the primer, the safer it is."
[0040] In a specific embodiment of the present invention, the resistance increase factor K of the base coating after heating at 130°C is 4~20, where K is the ratio of the sheet resistance of the base coating after heating at 130°C to the sheet resistance at 25°C; specifically, K can be 4, 8, 12, 16, 20, or any value between the two mentioned above. The resistance increase factor K characterizes the dynamic current limiting response capability of the base coating when heated. Its physical source is the structural change of the base coating material when heated—for example, the melting of the crystalline phase of the positive temperature coefficient polymer matrix and volume expansion, which breaks the percolation network of the conductive filler—resulting in a sudden increase in resistance. The larger K is, the greater the increase in resistance of the base coating and the stronger the current limiting when an internal short circuit occurs; however, an excessively large K means that the base coating is too sensitive to temperature changes, and a local temperature rise under normal high-rate operating conditions may falsely trigger the base coating to open the circuit, resulting in a sudden increase in internal resistance, a drop in capacity, or power loss. The present invention uses the resistance increase factor K of the base coating after heating as a dynamic fingerprint of "thermal trigger current limiting" and sets an upper limit to avoid false triggering of the circuit at normal high rates.
[0041] In a specific embodiment of the present invention, the compaction density of the positive electrode sheet is 3.20 g / cm³. 3 ~3.60g / cm 3 Specifically, it could be 3.20 g / cm³ 3 3.30g / cm 3 3.40 g / cm 3 3.50g / cm 3 3.60g / cm 3 , and any value between the two mentioned above. When the compaction density is too low, the interface contact between the bottom coating and the positive electrode active material layer is insufficient, the porosity is too high, the energy density is low, and the contact deteriorates during cycling; when the compaction density is too high, the electrode sheet is too brittle, and the winding is prone to cracking. The low porosity hinders lithium-ion transport, and the rate and cycle performance drops sharply.
[0042] In a specific embodiment of the present invention, the lithium-ion cylindrical battery adopts a full-tab laser-welded structure, with a full-tab welding coverage rate of η, where η is the ratio of the laser-welded area of the tab to the effective area of the tab end face. A full-tab laser-welded structure refers to a design where the positive and / or negative tabs use a full-tab design, and the electrical connection between the tabs and the current collector or casing is achieved through laser welding. The full-tab structure distributes the current collection path across the entire tab end face, resulting in a shorter current path and lower collection resistance compared to traditional single-tab or multi-tab structures. This helps reduce the battery's DC internal resistance and improves high-rate charge / discharge performance. A higher welding coverage rate η results in a larger effective conductive area on the tab end face, more uniform current collection, and lower battery internal resistance. η ≥ 80% ensures sufficient effective conductive area on the tab end face, enabling uniform current collection, low battery internal resistance, and providing a sufficient η base for SPI compliance, ensuring that the safety range of SPI ≥ 3.2 is still met even when K is at a low value.
[0043] In a specific embodiment of the present invention, the lithium-ion cylindrical battery satisfies the internal short-circuit protection index SPI = K × η ≥ 3.2, preferably SPI = 3.2~17. The lower limit of SPI is 3.2, which is the critical value to satisfy the full-charge state needle penetration safety and hot box safety. Below this value, the combined effect of thermal current limiting response and welding coverage is insufficient to suppress thermal runaway. The upper limit of SPI is 17. If SPI is too high, it means that K and / or η are too large. Especially when K is too high, the local temperature rise of the bottom coating under normal high-rate conditions may trigger a sudden increase in resistance, resulting in a sudden change in internal resistance, a drop in capacity, or power loss. Setting the upper limit of SPI to 17 can ensure sufficient internal short-circuit current limiting protection while avoiding the risk of false triggering under normal operating conditions.
[0044] In this invention, an undercoat layer is formed between the positive electrode current collector and the positive electrode active material layer. The thickness, room-temperature surface resistivity R, resistance increase factor K after heating, and positive electrode sheet compaction density of the undercoat layer are defined. At room temperature, the undercoat layer maintains a moderate surface resistivity to ensure low polarization under normal conditions. However, when an internal short circuit causes a localized temperature rise, the resistance of the undercoat layer increases significantly, forming a high-resistivity current-limiting channel near the short-circuit point. This suppresses short-circuit current, delays or blocks thermal runaway, and ensures the battery's thermal safety and energy density. Furthermore, by defining an internal short-circuit protection index (SPI) and requiring SPI ≥ 3.2, the thermal resistance response capability of the undercoat layer is coupled and constrained with the full-tab welding coverage. This ensures that, under the low internal resistance structure of the full-tab, the thermal current-limiting response and the coverage of the current collection path are synergistically matched. This ensures both full-charge needle penetration safety and hot box safety while maintaining low internal resistance and cycle life under normal conditions. Simultaneously, a low-cost evidence-based criterion for full-tab internal short-circuit current-limiting protection is established.
[0045] The characteristics of parameters such as the thickness, surface resistivity, and thermal resistance increase factor of the primer coating have been explained above. The material system of the primer coating will be further explained below.
[0046] In a specific embodiment of the present invention, the base coating layer includes one or more of the following: a composite layer containing a polymer matrix with a positive temperature coefficient and a conductive filler, an insulating-semi-conductive layer dispersed with nano-alumina, and a polyimide (PI)-based high-resistivity layer.
[0047] In a specific embodiment of the present invention, when the base layer is a composite layer containing a positive temperature coefficient (PTC) polymer matrix and conductive fillers, the PTC polymer matrix maintains the percolation network of the conductive fillers at room temperature, providing a suitable sheet resistance. When an internal short circuit causes a local temperature rise, the crystalline phase of the PTC polymer matrix melts and expands in volume, breaking the percolation network of the conductive fillers, causing a sharp increase in the resistance of the base layer, thus achieving dynamic current limiting. The room temperature sheet resistance of this composite layer can be controlled by the content of conductive fillers, and the increase in thermal resistance can be controlled by the crystallinity of the PTC polymer matrix; both can be set independently.
[0048] In a specific embodiment of the present invention, when the base coating is a composite layer containing a polymer matrix with a positive temperature coefficient and a conductive filler, the conductive filler can be conductive carbon black, carbon nanotubes, graphene, etc. The mass fraction of the conductive filler is 1% to 10%, specifically 1%, 3%, 5%, 7%, 9%, 10%, or any value between these two. The mass fraction of the conductive filler determines the room-temperature surface resistivity R of the base coating through the percolation network density. The higher the mass fraction, the denser the conductive network, the lower the R, and the smaller the normal polarization; the lower the mass fraction, the higher the R, the stronger the current-limiting ability, but the greater the normal polarization. The mass fraction of the conductive filler can be determined by thermogravimetric analysis (TGA) or ash content method.
[0049] In a specific embodiment of the present invention, when the base coating is a composite layer containing a positive temperature coefficient polymer matrix and conductive fillers, the positive temperature coefficient polymer matrix can be high-density polyethylene (HDPE), grafted polyolefin, low-density polyethylene, random copolymer polypropylene, or highly crystalline polyolefin after annealing and crystallization treatment, etc. The crystallinity of the positive temperature coefficient polymer matrix is 30%~82%, specifically 30%, 50%, 60%, 70%, 82%, and any value between the above two. The crystallinity of the PTC polymer matrix determines the intensity of the molten volume expansion of the crystalline phase when heated, and thus determines the degree of damage to the percolation network of the conductive fillers and the increase in thermal resistance by a factor K. When the crystallinity is too low, there is almost no obvious crystalline molten expansion when heated, and the PTC current-limiting response is insufficient; when the crystallinity is too high, the melting range is extremely narrow, and the conductive network suddenly breaks down in an extremely narrow temperature range when heated, which can easily trigger a circuit break under normal high-rate operating conditions. The crystallinity of the PTC polymer matrix can be calculated by measuring the melting enthalpy using differential scanning calorimetry (DSC) and the relative enthalpy of complete crystallization.
[0050] In this invention, the crystallinity of the PTC polymer matrix mainly affects the increase factor K of the thermal resistance, and the mass fraction of the conductive filler mainly affects the surface resistance K at room temperature. By limiting the range of these two parameters, the current-limiting performance and normal conductivity of the base coating can be controlled.
[0051] In a specific embodiment of the present invention, when the base layer is an insulating-semi-conductive layer dispersed with nano-alumina, the nano-alumina forms an insulating-semi-conductive composite structure in the base layer, providing a certain surface resistance at room temperature. When heated, the resistance further increases due to differences in the thermal expansion coefficients of the materials or changes in the interface, thereby achieving current limiting protection.
[0052] In a specific embodiment of the present invention, when the base coating is a PI-based high-resistivity layer, the PI-based material has excellent heat resistance and electrical insulation. As a base coating substrate, it can maintain high resistance characteristics over a wide temperature range, which helps to provide a stable current-limiting channel during internal short circuits.
[0053] In a specific embodiment of the present invention, the base coating further includes an adhesive, which includes one or more of polyvinylidene fluoride and its copolymers, polyacrylic acid, polyimide, polyacrylonitrile, polyurethane, sodium carboxymethyl cellulose and styrene-butadiene rubber.
[0054] In a specific embodiment of the present invention, the positive electrode active material layer includes a positive electrode active material, the chemical formula of which is LiNi. x Co y Mn zO2, where 0.8 ≤ x < 1, x + y + z = 1. This positive electrode active material belongs to the high-nickel material category of lithium-cobalt-manganese ternary materials (NCM), such as 8-series (x approximately 0.8) or 9-series (x approximately 0.9) high-nickel materials. High-nickel ternary positive electrode active materials (x ≥ 0.8) have high specific capacity, which is beneficial for improving the energy density of the battery; however, high-nickel systems have relatively poor thermal stability under full charge, and the oxygen release temperature during internal short circuits is low, making the requirements for internal short circuit protection more stringent. The current-limiting protection design of the bottom coating in this application, combined with the high-nickel positive electrode, effectively suppresses the risk of thermal runaway caused by internal short circuits by leveraging the high energy density advantage of high-nickel materials and through the thermal current-limiting response of the bottom coating.
[0055] In a specific embodiment of the present invention, the positive electrode active material layer further includes a positive electrode conductive agent and a positive electrode binder. The positive electrode conductive agent includes, but is not limited to, one or more of conductive carbon, conductive carbon black, conductive graphite, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers; the positive electrode binder includes, but is not limited to, one or more of polyvinylidene fluoride (PVDF), carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS). The present invention does not impose any special restrictions on the source of the above-mentioned positive electrode conductive agent and positive electrode binder; commercially available products well known to those skilled in the art can be used.
[0056] In a specific embodiment of the present invention, the method for preparing the positive electrode sheet includes: thoroughly mixing a positive electrode active material, a positive electrode binder, a positive electrode conductive agent, and a positive electrode solvent to prepare a slurry; coating the slurry onto a positive electrode current collector; and drying, cold pressing, and slitting to obtain the positive electrode sheet. The positive electrode current collector can be a metal foil such as aluminum foil, and the positive electrode solvent can be N-methylpyrrolidone (NMP).
[0057] In a specific embodiment of the present invention, the winding core further includes a negative electrode sheet and a separator.
[0058] In a specific embodiment of the present invention, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on at least one side surface of the negative electrode current collector. The negative electrode active material layer includes a negative electrode active material, a negative electrode conductive agent, and a negative electrode binder. The negative electrode active material includes silicon-carbon composite material and / or graphite; the negative electrode conductive agent includes, but is not limited to, one or more of conductive carbon, conductive carbon black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers; the negative electrode binder includes, but is not limited to, one or more of polyvinylidene fluoride (PVDF), carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS). The present invention does not impose any special restrictions on the source of the above-mentioned negative electrode active material, negative electrode conductive agent, and negative electrode binder; commercially available products well known to those skilled in the art can be used.
[0059] In a specific embodiment of the present invention, the method for preparing the negative electrode sheet includes: thoroughly mixing a negative electrode active material, a negative electrode binder, a negative electrode conductive agent, and a negative electrode solvent to prepare a slurry; coating the slurry onto a negative electrode current collector; and drying, cold pressing, and slitting to obtain the negative electrode sheet. The negative electrode current collector can be a metal foil such as copper foil, and the negative electrode solvent can be deionized water.
[0060] In a specific embodiment of the present invention, the separator includes a base membrane and a coating disposed on at least one surface of the base membrane; the base membrane preferably includes at least one of polypropylene (PP) film, polyethylene (PE) film, and PP / PE / PP composite film; the coating is preferably a ceramic coating and / or a PVDF coating. The present invention does not impose any special restrictions on the source of the separator; commercially available products or homemade products well known to those skilled in the art can be used.
[0061] In a specific embodiment of the present invention, the lithium-ion cylindrical battery is a 21650 cylindrical battery, that is, a cylindrical battery with an outer diameter of approximately 21 mm, a total height of approximately 65 mm, and a core height of 62.3 mm. The 21650 cylindrical battery has standardized dimensions, facilitating module integration and thermal management design. This specification employs a full-tab structure, resulting in a short current collection path and low internal resistance. Combined with the current-limiting protection design of the bottom coating, high energy density and internal short-circuit safety protection can be achieved simultaneously within a limited internal space.
[0062] In a specific embodiment of the present invention, the initial DC internal resistance DCR of the lithium-ion cylindrical battery is ≤10mΩ, which indicates that the introduction of the bottom coating does not significantly increase the ohmic internal resistance of the battery. The battery still maintains low polarization characteristics under normal conditions and has good high-rate charge and discharge capabilities.
[0063] In a specific embodiment of the present invention, the capacity retention rate of the lithium-ion cylindrical battery after 500 cycles at 1C rate at 25°C is ≥83%, which indicates that the bottom coating layer is structurally stable during long-term cycling and that the interface between the bottom coating layer and the positive electrode active material layer or the bottom coating layer itself is not degraded due to repeated charging and discharging. The cycle life of the battery meets the usage requirements.
[0064] In a specific embodiment of the present invention, the DC internal resistance growth rate of the lithium-ion cylindrical battery after 500 cycles at 1C rate at 25°C is ≤20%. This indicates that the bottom coating layer does not undergo significant conductive network degradation or interface contact deterioration during long-term cycling, and the power performance of the battery remains stable during the cycle life. It will not cause increased polarization or rate performance degradation due to the aging of the bottom coating layer.
[0065] In a specific embodiment of the present invention, the lithium-ion battery, in a fully charged state, undergoes a needle penetration test using a 3mm diameter steel needle at a penetration speed of 25mm / s. Within 300 seconds, the highest surface temperature remains ≤150℃, and no fire or explosion occurs. The fully charged needle penetration test simulates the extreme condition of a mechanically penetrating internal short circuit in the battery. At the moment of penetration, a large current and Joule heat are generated at the short circuit point. Near the short circuit point, the undercoat layer triggers a PTC response due to localized temperature rise, resulting in a sudden increase in resistance and forming a high-resistance current-limiting channel. This suppresses the short-circuit current, keeping the highest surface temperature below 150℃ within 300 seconds, thus preventing a thermal runaway chain reaction caused by oxygen release from the positive electrode active material and electrolyte decomposition.
[0066] In a specific embodiment of the present invention, the lithium-ion battery remained undamaged for 30 minutes during a 130°C hot box test without catching fire or exploding. The 130°C hot box test simulates the thermal abuse conditions of the battery under high-temperature environments. Under continuous high temperatures, the PTC characteristics of the undercoating layer maintain its resistance at a consistently high level. Even if the separator shrinks or partially breaks down at high temperatures, causing an internal short circuit, the undercoating layer can still limit the short-circuit current and prevent thermal runaway. This indicator verifies the effectiveness of the undercoating layer's current-limiting protection design under continuous high-temperature conditions from a thermal abuse perspective.
[0067] According to one aspect of the present invention, an electrical device is provided, comprising the lithium-ion cylindrical battery described in the above-described technical solution. Specifically, the lithium-ion battery can serve as a power source for the electrical device or as an energy storage unit for the electrical device. The electrical device may include, but is not limited to, mobile devices (e.g., mobile phones, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, energy storage systems, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships, and satellites. The following detailed description, in conjunction with specific embodiments, illustrates this application. However, the implementation and protection of this invention are not limited thereto. The following embodiments are merely some examples of this application and are not intended to limit the scope of this application. Where specific techniques or conditions are not specified in the embodiments, they shall be performed in accordance with the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments whose manufacturers are not specified are all commercially available conventional products. The silicon-carbon composite material was purchased from Zhiwei New Energy (Changzhou) Technology Co., Ltd., model SiSC-2A.
[0068] Example 1 S1. Preparation of the positive electrode: High-density polyethylene (HDPE) with 50% crystallinity, conductive carbon black, and polyvinylidene fluoride (PVDF) were mixed in a mass ratio of 90:5:5 and added to N-methylpyrrolidone (NMP). The mixture was dispersed at 3000 rpm for 4 hours, followed by vacuum degassing and filtration to obtain a base coating slurry. The base coating slurry was then applied to both sides of a 12µm thick aluminum foil treated with corona discharge using a micro-grooving roller. The dry film thickness of the base coating was controlled to 2µm by adjusting the coating gap. After pre-drying at 80℃, the coating was cured at 110℃ to obtain the base coating layer. The sheet resistivity R at 25℃ was measured to be 30Ω·cm using the four-probe method. 2 The resistance increase was measured to be K=8 after local heating of the base coating at 130℃.
[0069] NCM9055, conductive carbon black, and polyvinylidene fluoride were added to N-methylpyrrolidone at a mass ratio of 94:3:3. After thorough stirring, a positive electrode slurry with a solid content of 70% was obtained. The positive electrode slurry was then applied to aluminum foil with a pre-coated base layer via double-sided slit coating. After gradient drying, the slurry was cold-pressed until the compaction density of the positive electrode sheet reached 3.4 g / cm³. 3 The cathode is then vacuum dried to obtain the positive electrode sheet. The bottom coating layer has a continuous coverage of 98% along the aluminum foil coating area.
[0070] S2, Preparation of the negative electrode: 90 wt% silicon-carbon composite material, 5 wt% natural graphite, 2 wt% conductive carbon black, 1.2 wt% carboxymethyl cellulose, and 1.8 wt% styrene-butadiene rubber were added to deionized water and stirred thoroughly to obtain a negative electrode slurry. The negative electrode slurry was uniformly coated on both sides of a copper foil, dried, and then rolled to obtain a negative electrode sheet. The capacity ratio of the negative electrode sheet to the positive electrode sheet was N / P = 1.08.
[0071] S3. Preparation of electrolyte: In an argon-filled glove box (H2O < 0.1 ppm, O2 < 0.1 ppm), lithium hexafluorophosphate (LiPF6), ethylene carbonate (EC), dimethyl carbonate (DMC), fluoroethylene carbonate (FEC), and vinylene carbonate (VC) were mixed in a mass ratio of 14.0:25.0:51.0:6.0:4.0 and stirred until completely dissolved to obtain the electrolyte.
[0072] S4. Preparation of lithium-ion batteries: A 9µm thick PE membrane was selected as the base membrane, and a 1.5µm thick ceramic coating was coated on both sides of the base membrane. After drying, a 12µm thick separator was obtained with a porosity of 40%.
[0073] After the positive and negative electrode sheets are rolled and slit, they are wound together with the separator according to a set process to form a 21650 cylindrical battery core. The core is 62.3 mm high, 20 mm in diameter, and has a center hole diameter of 3.5 mm. The positive and negative tabs are laser-welded across the entire cross-section, with a full tab welding coverage of η=85%. The core is then placed in a nickel-plated steel shell, and after electrolyte injection, sealing, and formation, a 21650 full-tab cylindrical lithium-ion battery with an outer diameter of 21 mm and a total height of 65 mm is obtained.
[0074] Example 2 The difference between Example 2 and Example 1 is that in step S1, the thickness of the dry film of the base coating is 0.5µm.
[0075] Example 3 The difference between Example 3 and Example 1 is that in step S1, the thickness of the dry film of the base coating is 3µm.
[0076] Example 4 The difference between Example 4 and Example 1 is that in step S1, the thickness of the dry film of the base coating is 4µm.
[0077] Example 5 The difference between Example 5 and Example 1 is that in step S1, the thickness of the dry film of the base coating is 5µm.
[0078] Example 6 Example 6 differs from Example 1 in that, in step S1, the mass fraction of conductive carbon black in the base coating slurry is 10 wt%; R = 5 Ω·cm 2 .
[0079] Example 7 Example 7 differs from Example 1 in that, in step S1, the mass fraction of conductive carbon black in the base coating slurry is 6.5 wt%; R = 20 Ω·cm 2 .
[0080] Example 8 Example 8 differs from Example 1 in that, in step S1, the mass fraction of conductive carbon black in the base coating slurry is 3.5 wt%; R = 50 Ω·cm 2 .
[0081] Example 9 Example 9 differs from Example 1 in that, in step S1, the mass fraction of conductive carbon black in the base coating slurry is 2.5 wt%; R = 80 Ω·cm 2 .
[0082] Example 10 Example 10 differs from Example 1 in that, in step S1, high-density polyethylene (HDPE) with a crystallinity of 50% is replaced with low-density polyethylene with a crystallinity of 30%; K=4.
[0083] Example 11 Example 11 differs from Example 1 in that, in step S1, high-density polyethylene (HDPE) with a crystallinity of 50% is replaced with high-density polyethylene (HDPE) with a crystallinity of 62%; K=12.
[0084] Example 12 Example 12 differs from Example 1 in that, in step S1, high-density polyethylene (HDPE) with a crystallinity of 50% is replaced with high-density polyethylene (HDPE) with a crystallinity of 72%; K=16.
[0085] Example 13 Example 13 differs from Example 1 in that, in step S1, high-density polyethylene (HDPE) with a crystallinity of 50% is replaced with high-density polyethylene (HDPE) with a crystallinity of 82%; K=20.
[0086] Example 14 The difference between Example 14 and Example 1 is that, in step S1, the compaction density of the positive electrode sheet is 3.2 g / cm³. 3 .
[0087] Example 15 The difference between Example 15 and Example 1 is that, in step S1, the compaction density of the positive electrode sheet is 3.3 g / cm³. 3 .
[0088] Example 16 The difference between Example 16 and Example 1 is that, in step S1, the compaction density of the positive electrode sheet is 3.5 g / cm³. 3 .
[0089] Example 17 The difference between Example 17 and Example 1 is that, in step S1, the compaction density of the positive electrode sheet is 3.6 g / cm³. 3 .
[0090] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that in step S1, the thickness of the dry film of the base coating is 0.2µm.
[0091] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that in step S1, the thickness of the dry film of the base coating is 7µm.
[0092] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that, in step S1, the mass fraction of conductive carbon black in the primer slurry is 15 wt%; R = 2 Ω·cm 2 .
[0093] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that, in step S1, the mass fraction of conductive carbon black in the base coating slurry is 1 wt%; R = 150 Ω·cm 2 .
[0094] Comparative Example 5 The difference between Comparative Example 5 and Example 1 is that in step S1, high-density polyethylene (HDPE) with a crystallinity of 50% is replaced with random polypropylene (aPP) with a crystallinity of 12%; K=2.5.
[0095] Comparative Example 6 The difference between Comparative Example 6 and Example 1 is that in step S1, high-density polyethylene (HDPE) with a crystallinity of 50% is replaced with ultra-high crystallinity high-density polyethylene (HDPE) with a crystallinity of 90%; K=35.
[0096] Comparative Example 7 The difference between Comparative Example 7 and Example 1 is that, in step S1, the compaction density of the positive electrode sheet is 3.0 g / cm³. 3 .
[0097] Comparative Example 8 The difference between Comparative Example 8 and Example 1 is that, in step S1, the compaction density of the positive electrode sheet is 3.7 g / cm³. 3 .
[0098] Performance testing: The performance of the base coating, positive electrode, and lithium-ion battery prepared in Examples 1-17 and Comparative Examples 1-8 was tested, and the specific procedures are as follows: Undercoat thickness test: After discharging the finished battery to 0% state of charge, the positive electrode sheet was disassembled in a dry environment, cleaned with dimethyl carbonate (DMC), vacuum dried, polished by argon ion beam section, and observed by field emission scanning electron microscope (CP-SEM). The three-layer structure of aluminum foil / undercoat / positive electrode active material layer can be distinguished. The thickness of the undercoat is measured by taking the average value of multiple points with a micrometer.
[0099] Test of surface resistance and resistance rise factor of base coating at room temperature: Measure the surface resistance R (resistance per unit area) of aluminum foil coated with base coating (with the positive electrode active material layer removed) at room temperature (25℃) using a four-probe micro-ohmmeter; measure the resistance after locally heating the same sample to 130℃, and calculate K = surface resistance after heating / surface resistance at room temperature.
[0100] Cathode sheet compaction density determination: First, the cathode sheet, after being washed with dimethyl carbonate and vacuum dried, was cut into nine standard-sized square samples (2.0cm × 2.0cm). Next, the active material on both sides of three of these square samples was removed, rinsed with NMP, dried, weighed, and the average mass M1 was calculated. Simultaneously, the average thickness L1 of the samples was measured using a micrometer. Then, the mass of the remaining six square samples was weighed, and the average mass M2 was calculated. The average thickness L2 of the samples was also measured. The cathode sheet compaction density ρ was calculated using the following formula: ρ(g / cm 3 ) = (M2 - M1) / [A × (L2 - L1)]; Where A is the coating area on one side of the sample, A = 2.0cm × 2.0cm = 4.0cm 2 (L2-L1) represents the thickness of the positive electrode active material layer; M2-M1 represents the mass of the positive electrode active material layer.
[0101] Full tab welding coverage test: After discharging the finished battery to 0% state of charge, the core is disassembled in a dry environment. The laser welding imprint image of the tab end face is acquired by optical microscopy, and the percentage of the tab laser welding imprint area to the effective area of the tab end face is calculated, which is the full tab welding coverage η.
[0102] DC internal resistance (DCR) test: The test was conducted using an Arbin LBT battery testing system at 25°C and 50% SOC. The pulse current was 1C, the pulse duration was 10s, and the voltage drop ΔV was measured. The DCR under the initial conditions was calculated according to Ohm's law, and the ohmic internal resistance was verified by the high-frequency real intercept of electrochemical impedance spectroscopy (EIS).
[0103] Needle penetration test: The battery to be tested was fully charged to 100% SOC and placed in a 25℃ environment for 2 hours to stabilize. Then, the battery was fixed on an insulating clamp, ensuring its positive and negative terminals were horizontal. Using a 3mm diameter stainless steel needle, perpendicular to the battery surface and along the direction between the positive and negative terminals, the needle was inserted into the battery at a constant speed of 25mm / s until it was completely penetrated (the penetration depth must exceed 90% of the battery thickness). After insertion, the needle was kept still, and the battery status was continuously observed for 5 minutes. Any abnormal phenomena such as fire, explosion, or smoke were recorded. Temperature changes were monitored using a thermocouple attached to the battery surface, and the highest surface temperature T was recorded. The short-circuit current was also collected simultaneously.
[0104] Hot box test method: Place the lithium-ion battery in a 25℃ constant temperature chamber for 4 hours, charge it to 4.2V with a constant current and constant voltage of 1C, cutoff current of 0.1C, and let it stand for 10 minutes. Then, heat it to 130℃ at a rate of 5℃ / min and hold it at that temperature for 30 minutes. Passing requirement: No fire or explosion.
[0105] Cyclic performance test: The battery was placed in a 25℃ constant temperature chamber for 6 hours, followed by a first cycle of constant current and constant voltage charging (1.0C to 4.2V, then constant voltage until the current drops to 0.05C), a 30-minute rest period, and then constant current discharging (1.0C to 2.5V). A total of 500 charge-discharge cycles were performed. The discharge capacities Q1 and Q2 after 1 and 500 cycles were calculated. 500 Calculate the cycle capacity retention rate % = (Q 500 / Q1)×100%.
[0106] 5C Rate Performance Test: The lithium-ion battery was placed in a 25℃ constant temperature chamber for 4 hours, then charged at 1C constant current and constant voltage to 4.2V, with a cutoff current of 0.1C, and allowed to stand for 30 minutes. It was then discharged at 0.2C constant current to 2.5V cutoff, and allowed to stand for 30 minutes. The discharge capacity was recorded. The battery was then charged at 1C constant current and constant voltage to 4.2V, with a cutoff current of 0.1C, and allowed to stand for 30 minutes. It was then discharged at 5C constant current to 2.5V cutoff, and the discharge capacity was recorded. Any abnormalities were observed during the charging and discharging process. The 5C rate capacity retention rate was calculated as (5C discharge capacity / 0.2C discharge capacity) × 100% to quantitatively evaluate the rate performance.
[0107] Energy density test: The lithium-ion battery was placed at 25°C and charged to 4.2V under constant current and constant voltage conditions at 0.2C. The cutoff current was 0.02C. After standing for 5 minutes, it was discharged to 2.5V at 0.2C, and the battery energy E was recorded. The energy density relative to the energy density of other examples and comparative examples was recorded with the energy density of Example 1 as 100% as the baseline.
[0108] The test data is shown in Table 1.
[0109] Table 1 Test results of the examples and comparative examples Referring to Table 1, it can be seen from Examples 1-5 and Comparative Examples 1-2 that the thickness of the undercoat layer determines the geometric thickness of the current-limiting layer and its series current-limiting capability. A thicker undercoat layer results in a longer high-resistance current-limiting channel near the short-circuit point during internal short circuits, leading to stronger current limiting and a decrease in the maximum fully charged needle penetration temperature from 145°C to 110°C. In Comparative Example 1, the undercoat layer was too thin, resulting in insufficient continuous coverage and current limiting, leading to needle penetration thermal runaway and a maximum surface temperature of 234°C. In Comparative Example 2, the undercoat layer was too thick; while safe for needle penetration testing, it increased the positive electrode series resistance, occupied the internal cavity of the 21650 cylindrical battery, and reduced energy density by 8%. Furthermore, Comparative Example 2's 5C rate capacity retention was 70%, significantly lower than Example 1's 92%, indicating that excessive thickness significantly increases the positive electrode series resistance, leading to a decrease in rate performance.
[0110] As can be seen from Examples 1, 6-9, and Comparative Examples 3-4, the surface resistance R of the base coating at room temperature is determined by the mass fraction of conductive carbon black in the base coating and the percolation network density: the higher the mass fraction of conductive carbon black, the denser the conductive network, the lower the surface resistance of the base coating at room temperature, the smaller the normal polarization, but the weaker the internal short-circuit current limiting; the lower the mass fraction of conductive carbon black, the higher the surface resistance of the base coating at room temperature, the stronger the current limiting, but the greater the normal DCR and polarization. In Comparative Example 3, the mass fraction of conductive carbon black was too high, the conductive network was too dense, and the surface resistance of the base coating at room temperature was 2 Ω·cm. 2 The undercoat layer, being almost a conductive layer, had virtually no current-limiting effect, leading to ignition during the needle penetration test, with the highest surface temperature reaching 238℃. In Comparative Example 4, the conductive carbon black mass fraction was too low, resulting in an excessively sparse conductive network. The 5C rate capacity retention was only 60%, and the initial DCR was as high as 12.5 mΩ, failing to meet both rate and capacity standards. This confirms the adverse effects of the excessively high surface resistivity of the undercoat layer at room temperature on normal performance.
[0111] As can be seen from Examples 1, 10-13, and Comparative Examples 5-6, the resistance increase factor K after heating is not directly set, but is determined by the crystallinity of the PTC polymer matrix. Its physical source is the melting and volume expansion of the crystalline phase when the matrix is subjected to short-circuit Joule heating, which breaks the percolation network of the conductive carbon black, causing a sudden increase in resistance. The higher the crystallinity of the PTC polymer matrix, the greater the melt expansion, the stronger the percolation network disruption, and the greater the resistance increase factor (while the conductive filler is finely adjusted to maintain R = 30 Ω·cm). 2Comparative Example 5, with a near-amorphous matrix and a crystallinity of 12%, exhibited almost no melt expansion, insufficient PTC response, an SPI of 2.125 < 3.2, and a maximum surface temperature of 232°C during the needle penetration test, resulting in thermal runaway. Comparative Example 6, with a crystallinity of 90%, had an extremely narrow melting range, leading to a sudden break in the heating network, resulting in excessively high K values. Under normal 5C high-rate localized temperature rise, it falsely triggered a circuit break, causing a capacity drop and power loss.
[0112] As can be seen from Examples 1, 14-17, and Comparative Examples 7-8, the compaction density of the positive electrode affects normal conductivity, energy density, and cycle life through the interface contact between the undercoat layer and the positive electrode active material layer, as well as the electrode porosity. The compaction density of Comparative Example 7 is too low, only 3.0 g / cm³. 3 The interface contact is insufficient, the porosity is high, the energy density is low, and the cyclic contact deteriorates. The compaction density of Comparative Example 8 is too high, at 3.7 g / cm³. 3 The positive electrode sheet was too brittle, resulting in winding cracks. Furthermore, its 5C rate capacity retention rate was 75%, and the capacity retention rate after 500 cycles was significantly lower than the 87.2% of Example 1. This indicates that the excessively high compaction density resulted in excessively low porosity and hindered ion transport, leading to a sharp drop in rate and cycle performance.
[0113] The parts of this invention not described in detail are techniques known to those skilled in the art.
[0114] The basic principles of the present invention have been described above with reference to specific embodiments. However, it should be noted that the advantages, benefits, and effects mentioned in the present invention are merely examples and not limitations, and should not be considered as essential features of each embodiment of the present invention. Furthermore, the specific details disclosed above are for illustrative and facilitative purposes only, and are not limitations. These details do not limit the present invention to the necessity of employing the aforementioned specific details.
[0115] In the foregoing description of this specification, references to terms such as "one embodiment," "another embodiment," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment is included in at least one embodiment of this application. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. Moreover, those skilled in the art can combine and integrate the different embodiments or examples described in this specification, as well as the features of different embodiments or examples, without contradiction. Additionally, it should be noted that in this specification, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of indicated technical features.
[0116] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A lithium-ion cylindrical battery, characterized in that, The device includes a core, the core including a positive electrode sheet, the positive electrode sheet including a positive current collector, a positive active material layer disposed on at least one side of the positive current collector, and a base coating layer disposed between the positive current collector and the positive active material layer; The thickness of the base coating is 0.5µm to 5µm; The sheet resistance of the base coating at 25°C is R = 5 Ω·cm. 2 ~80Ω·cm 2 ; The resistivity increase factor K of the base coating after heating at 130°C is 4~20, where K is the ratio of the surface resistivity of the base coating after heating at 130°C to the surface resistivity at 25°C. The compaction density of the positive electrode is 3.20 g / cm³. 3 ~3.60g / cm 3 ; The lithium-ion cylindrical battery has a full tab laser welding structure, and the full tab welding coverage is η, where η is the ratio of the tab laser welding area to the effective area of the tab end face. The lithium-ion cylindrical battery satisfies the internal short-circuit protection index SPI=K×η≥3.
2.
2. The lithium-ion cylindrical battery according to claim 1, characterized in that, The required η ≥ 80%.
3. The lithium-ion cylindrical battery according to claim 1, characterized in that, SPI = 3.2~17.
4. The lithium-ion cylindrical battery according to claim 1, characterized in that, The base coating includes one or more of the following: a composite layer containing a polymer matrix with a positive temperature coefficient and conductive filler, an insulating-semi-conductive layer dispersed with nano-alumina, and a polyimide-based high-resistivity layer.
5. The lithium-ion cylindrical battery according to claim 4, characterized in that, The crystallinity of the positive temperature coefficient polymer matrix is 30%~82%; And / or, the mass fraction of the conductive filler is 1% to 10%.
6. The lithium-ion cylindrical battery according to claim 1, characterized in that, The positive electrode active material layer includes a positive electrode active material, the general chemical formula of which is LiNi. x Co y Mn z O2, where 0.8≤x<1, x+y+z=1; And / or, the core further includes a negative electrode sheet, the negative electrode sheet including a negative electrode active material, the negative electrode active material including silicon-carbon composite material and / or graphite.
7. The lithium-ion cylindrical battery according to claim 1, characterized in that, The lithium-ion cylindrical battery has an outer diameter of 21 mm, a total height of 65 mm, and a core height of 62.3 mm. And / or, the initial DC internal resistance of the lithium-ion cylindrical battery is ≤10mΩ; And / or, the DC internal resistance growth rate of the lithium-ion cylindrical battery after 500 cycles at 1C rate at 25°C is ≤20%; And / or, the capacity retention rate of the lithium-ion cylindrical battery after 500 cycles at 1C rate at 25°C is ≥83%.
8. The lithium-ion cylindrical battery according to claim 1, characterized in that, The lithium-ion battery, when fully charged, was subjected to a needle puncture test with a steel needle of 3 mm diameter at a puncture speed of 25 mm / s. Within 300 seconds, the highest surface temperature was ≤150℃, and no fire or explosion occurred. And / or, the lithium-ion battery did not catch fire or explode after being kept in a 130°C hot box test for 30 minutes.
9. The lithium-ion cylindrical battery according to claim 1, characterized in that, The base coating also includes an adhesive, which includes one or more of polyvinylidene fluoride and its copolymers, polyacrylic acid, polyimide, polyacrylonitrile, polyurethane, sodium carboxymethyl cellulose, and styrene-butadiene rubber.
10. An electrical appliance, characterized in that, Including the lithium-ion cylindrical battery as described in any one of claims 1 to 9.